2017
DOI: 10.1038/s41467-017-01364-z
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog mediated degradation of Ihog adhesion proteins modulates cell segregation in Drosophila wing imaginal discs

Abstract: The Drosophila Hedgehog receptor functions to regulate the essential downstream pathway component, Smoothened, and to limit the range of signaling by sequestering Hedgehog protein signal within imaginal disc epithelium. Hedgehog receptor function requires both Patched and Ihog activity, the latter interchangeably encoded by interference hedgehog (ihog) or brother of ihog (boi). Here we show that Patched and Ihog activity are mutually required for receptor endocytosis and degradation, triggered by Hedgehog prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 81 publications
0
39
0
Order By: Relevance
“…Moreover, receiving-cell cytonemes over-expressing Dally or Dlp acquire stability when interacting with cytonemes over-expressing the co-receptor Ihog and emanating from Hh producer cells, indicating a potential role for HSPG/Ihog interaction in trans during cytoneme growth [ 13 ]. Additionally, a recent publication describes a novel role for the Hh co-receptors Ihog/Boi in cell adhesion, where they are crucial for correct segregation of posterior and anterior cell populations [ 119 ]. Ihog retains Hh on the cell surface mainly at the basolateral side of the Drosophila wing disc for distribution, presentation and subsequent signal reception at cytoneme contacts [ 13 ].…”
Section: Basal Formation Of Cytonemes and The Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, receiving-cell cytonemes over-expressing Dally or Dlp acquire stability when interacting with cytonemes over-expressing the co-receptor Ihog and emanating from Hh producer cells, indicating a potential role for HSPG/Ihog interaction in trans during cytoneme growth [ 13 ]. Additionally, a recent publication describes a novel role for the Hh co-receptors Ihog/Boi in cell adhesion, where they are crucial for correct segregation of posterior and anterior cell populations [ 119 ]. Ihog retains Hh on the cell surface mainly at the basolateral side of the Drosophila wing disc for distribution, presentation and subsequent signal reception at cytoneme contacts [ 13 ].…”
Section: Basal Formation Of Cytonemes and The Extracellular Matrixmentioning
confidence: 99%
“…It is this Ptc/Hh endocytosis that directs Ihog to degradation in receiving cells, resulting in a protein spatial pattern that is the reverse of Ptc expression, with less Ihog on the Hh signalling region [ 119 ]. These decreased Ihog levels seem to reduce cell–cell adhesion [ 119 ] and, interestingly, this coincides with the locations where Hh cytoneme extension would take place [ 9 , 13 ]. In summary, the extracellular matrix provides the substrate for cytonemes to extend.…”
Section: Basal Formation Of Cytonemes and The Extracellular Matrixmentioning
confidence: 99%
“…In turn, Ptc is also up-regulated in a graded manner, being itself a transcriptional target of the Hh pathway (Chen & Struhl, 1996;Briscoe et al, 2001;Torroja et al, 2005). As for the co-receptors Ihog and Boi (Bilioni et al, 2013), they are found in both Hh-producing and Hh-receiving cytonemes, maintaining Hh levels for correct reception (Zheng et al, 2010;Hsia et al, 2017). Other components necessary for Hh reception, including Dispatched (Disp) (Burke et al, 1999;Ma et al, 2002), the Wif ortholog Shifted (Shf) (Glise et al, 2005;Gorfinkiel et al, 2005), and the glypicans Dally-like (Dlp) (Desbordes & Sanson, 2003;Lum et al, 2003a) and Dally (Takeo et al, 2005), are all localized in cytonemes (Callejo et al, 2011;Bilioni et al, 2013;Gonzalez-Mendez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments show that mixing cells from different tissues in vitro leads to their segregation, with initially fuzzy borders that sharpen in time [55]. This has been observed for many systems for instance in the development of the wing imaginal disc in Drosophilia [34], in the developing nervous system [29] etc. So far, three types of mechanisms have been identified to have a role in segregation and border formation, namely (i) differential adhesion, (ii) contact cell repulsion and (iii) cortical tension.…”
mentioning
confidence: 71%
“…4 I) we observe that the constant steady state is unstable again only for sufficiently small z 1,0 and iff ∆(M 1,0 ) < 0. This leads to two eigenvalues λ 1 , λ 2 of different signs, that can be computed using the formulas (34). The value of parameter s that corresponds to the phase transition can be computed by equating (42) to 0 and therefore…”
Section: 2mentioning
confidence: 99%